Adrift (2009) [videorecording (DVD)] - Dhalia, Heitor, 1970- (Universal Studios Home Entertainment, 2011)
While spending summer vacation with her family on the idyllic southeast coast of Brazil, fourteen-year-old Filipa discovers that her father, a famous author, is betraying her mother by dallying with a beautiful young American woman. Wrestling with the truth, Filipa will soon discover that her father's infidelity is only the first of many dark secrets that lurk beneath the surface of her seemingly perfect family.